Analysis of the water management of the Poilão dam in Cape Verde - Oliveira, Rubmara Ketzer; Meirelles, Fernando Setembrino Cruz; Lopes, Tárcio Rocha (Revista Hipótese, 2020)
Water is a decisive element for economic and social progress. The objective of this work is to develop instruments to assist in the management of water for irrigation in the Poilão dam in Cabo Verde, aiming at the conscious and planned use of water by farmers for irrigation. The main activities were the monitoring of the dam management processes and their influence in each irrigated area and a research on the use of water for irrigation, being possible to carry out an evaluation of the dam management process and presentation of alternatives to assist in the development of the same.